Chronopharmacology of roflumilast: a comparative pharmacokinetic study of morning versus evening administration in healthy adults - Bethke, Thomas D.; Huennemeyer, Andreas; Lahu, Gezim; Lemmer, Björn (Chronobiology international, 2010)
The human circadian system is known to affect the pharmacokinetics and pharmacodynamics of several classes of respiratory disease medications. The current study involving 16 healthy adults investigated if the time-of-day of dosing of roflumilast, a novel phosphodiesterase-4 inhibitor, affects its pharmacokinetics. The rate of drug absorption (tmax: 1.50 versus 2.00 h) and peak concentration at tmax (Cmax: 3.79 versus 3.06 µg/L) was slightly greater with morning than evening administration, but without clinical significance. The extent of drug absorption (AUC) and drug elimination (t1/2) did not differ between the two dosing times. The pharmacokinetics of the active main metabolite, roflumilast N-oxide, also was not affected by the time of drug administration. Finally, the safety and tolerability of roflumilast did not differ between the two different times of administration. (E-mail correspondence: thomas.bethkenycomed.com)
Gesehen am 27.01.2023